The Implementation of Cultural Dimensions in The â€œBahasa Inggrisâ€ English Textbook for Eleventh Graders - Auladi, Ahmad Yusron; Rukmini, Dwi; Sutopo, Djoko (Universitas Negeri Semarang, 2019)
This study aims at explaining the implementation of the cultural dimensions in the textbook. There are four cultural dimensions analysed in this research, they are product, practice, perspective, and person (Moran, 2001). Product dimension refers to goods and services. Practice dimension refers to how the member of culture manipulates the product. Perspective dimension refers to perceptions, beliefs, and attitudes. Person dimension refers to the personal experience and story of the cultural members. This study applied descriptive qualitative research with interactive data analysis, consisting of (1) data collection, (2) data reduction, (3) data interpretation, and (4) conclusion (Miles & Huberman, 1994). In this study, it is found that the author of the textbook implemented the cultural dimensions by inserting text and pictures that are related to the cultural dimensions. From the results of the research, it can be concluded that cultural products dominated the content of the textbook.